2022
DOI: 10.1002/joc.7563
|View full text |Cite
|
Sign up to set email alerts
|

Links between precipitation, circulation weather types and orography in central Italy

Abstract: Recent analyses of satellite and surface observations reported a negative annual rainfall trend in central Italy. The complex orography of the Apennines and the strong influence of climate change in the Mediterranean basin complicates the explanation of such trends and their spatial variability. This work aims at describing the link between circulation weather types, orography and precipitation patterns observed in central Italy, as a first step towards the understanding of such climate trends. Using ERA5 rean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…For what it concerns the biases in precipitation, the results obtained here are in line with what has been found in Central Italy where discrepancies between observations and ERA5 reanalysis precipitation have been noticed in general, and specifically in the Trasimeno lake area, where yearly mean precipitation is overestimated by ERA5 reanalyses [74]. Moreover, in the literature, precipitation biases of ERA5 have been noted in other parts of the world.…”
Section: Discussionsupporting
confidence: 91%
“…For what it concerns the biases in precipitation, the results obtained here are in line with what has been found in Central Italy where discrepancies between observations and ERA5 reanalysis precipitation have been noticed in general, and specifically in the Trasimeno lake area, where yearly mean precipitation is overestimated by ERA5 reanalyses [74]. Moreover, in the literature, precipitation biases of ERA5 have been noted in other parts of the world.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the disadvantage of managing a larger dataset is not always balanced by an improvement in terms of accuracy. As regards precipitation, it is more difficult to represent its erratic spatial distribution; a study over Central Italy (period: 1951-2019), has shown that ERA5 generally overestimates the annual rainfall, except on the north-central Apennines where it is underestimated [10] . Anyway, with reference to several Italian irrigation districts, a general good agreement was obtained between observed and reanalysis (ERA5 and ERA5 Land) derived agrometeorological variables at both daily and seasonal scales [9] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The circulation weather type classification is the same as in Silvestri et al (2022a). Daily circulation weather types (CWT) are classified by using mean sea level pressure (MSLP) as the classification variable and obliquely rotated principal components in T-mode (PCT), also called principal component analysis in T-mode (TPCA), as the classification method.…”
Section: Circulation Weather Types Classificationmentioning
confidence: 99%